Evolution of entrepreneurship by opportunity in the city of Babahoyo: : period 2020-2021 - Mora-Aristega, Julio Ernesto; Sandoval-Pérez, María José; Coello-Vásquez, Vicente Javier; Morales-Morejón, Silvia Elizabeth (Revista Colón Ciencias, Tecnología y Negocios, 2023)
Entrepreneurship is defined as an individual’s initiative to develop a business idea that generates income. This activity has significantly contributed to the economy of several cities in Ecuador. Undoubtedly, it is the path to prosperity that is pressing in these times when the government as a provider of employment and salaries is already overwhelmed in its capacity. Based on this premise, the present research aims to analyze the evolution of opportunity-driven entrepreneurship in the period between 2020-2021 in the city of Babahoyo to identify, understand, and examine the various opportunities recognized and utilized by entrepreneurs, as well as the factors that influenced the performance, evolution, and success of the ventures within this period. The methodology used was analytical, descriptive, and exploratory, employing semi-structured surveys with dichotomous and quantitative variables, as well as interviews with open-ended questions with 10 sustainable entrepreneurs from the city. According to the study, it was concluded that 80% of the entrepreneurs identified an opportunity in their environment to develop an innovative business idea that allowed them to grow in the market. With the help of entrepreneurial competences, 50% of the entrepreneurs cultivate competences such as quality, efficiency, and persistence in their businesses. 50% of the respondents consider the most important competence when starting a business to be the search for opportunities and initiative, followed by 20% who consider goal setting and information search as essential competences.